EFEKTIVITAS PEMBERIAN CGF 40% DALAM MEMPERCEPAT PENINGKATAN TROMBOSIT PADA PENDERITA DEMAM BERDARAH DENGUE - Adi Teruna Effendi; M Sediono; HS Suksmono; B Erwanto; Yekti Hartati Effendi; Mira Dewi; Darwin Karyadi (Food and Nutrition Society of Indonesia, 2010)
Aim of this study was to evaluate the effectiveness of CGF 40% in hastening the recuperation, as indicated by reduced length of hospital stay, improvement in clinical status, increase in platelets, and reduction in the hemoconcentration. The study group comprised of 84 consecutive DHF patients, 42 male and 42 female subjects, who were randomized into the control group receiving the WHO standard therapy and the intervention group receiving CGF 40% and the standard therapy. Hemoglobin, hematocrite and thrombocyte counts were taken daily until the subjects were free of the symptoms and signs of DHF, and the thrombocyte count read >100.000. The results were analyzed statistically, student t test and quadratic regression, using SPSS 16 software. The average length of recuperation time in the intervention and control groups were 2.76 days and 4.43 days respectively (p=0.000). Recuperation times of subjects with thrombocyte counts <50,000 and >50,000 of the intervention group (3,09 and 2,37 days) and the control group (4,2 and 4,5 days) were different significantly (p=0.016 and 0.000). When analized specifically in the treatment group, the recuperation time of those with thrombocyte counts <50,000U (2.37 days) did not differ to those with >50,000 (3.09 days) with p=0.112. Using quadratic regression, the increase in thrombocytes, reduction in hemoglobin concentrations and hematocrite were faster in the intervention group when compared to the control group, with R2 almost reaching 1. The study disclosed that administration of CGF 40% could reduce the recuperation time and improved the hemoconcentration, which presumably demonstrated the concept of regenerative medicine as indicated by the repairmen of vascular permeability.